1996
DOI: 10.1007/bf02088228
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative activity of gastric epithelium in progressive stages ofHelicobacter pylori infection

Abstract: Helicobacter pylori (HP) infection is the main etiopathogenetic agent responsible for inflammatory and ulcerative changes in gastroduodenal mucosa and the basis for both intestinal and diffuse types of gastric carcinoma. In this latter case, intestinal metaplasia is the intermediary between gastritis and cancer. In this study we describe the proliferative activity of gastric epithelium in the progressive stages of HP infection. The expression of proliferating cell nuclear antigen (PCNA), which has proven to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 22 publications
3
25
2
Order By: Relevance
“…The results of these studies may be, in a certain way, compared with own studies according to which no significant influence of H.pylori colonization on proliferative activity of gastric mucosal glandular epithelium was demonstrated. An increase in proliferative activity of glandular epithelium in gastric mucosa was also observed in chronic gastritis, independently of its etiology (Bechi et al, 1996;Deschner et al, 1972;Irazusta et al, 1998;Panella et al, 1996). It was usually accompanied by a decrease in G cell count, including adrenomodulincontaining cells (Kitani et al, 1999), particularly frequently when the gastritis was associated with atrophic lesions.…”
Section: Analysis Of the Proliferative Activity Of Gastric Mucosa Glasupporting
confidence: 41%
See 2 more Smart Citations
“…The results of these studies may be, in a certain way, compared with own studies according to which no significant influence of H.pylori colonization on proliferative activity of gastric mucosal glandular epithelium was demonstrated. An increase in proliferative activity of glandular epithelium in gastric mucosa was also observed in chronic gastritis, independently of its etiology (Bechi et al, 1996;Deschner et al, 1972;Irazusta et al, 1998;Panella et al, 1996). It was usually accompanied by a decrease in G cell count, including adrenomodulincontaining cells (Kitani et al, 1999), particularly frequently when the gastritis was associated with atrophic lesions.…”
Section: Analysis Of the Proliferative Activity Of Gastric Mucosa Glasupporting
confidence: 41%
“…It is worth mentioning that other authors (Ito et al, 1986) found a deepening of proliferative zone within gastric glands in the same gastric mucosal inflammatory conditions, with accompanying significant reduction of EC cell number. According to some authors, increased proliferative activity of gastric mucosal glandular epithelium, particularly that measured by PCNA expression, in the course of chronic inflammatory conditions and H.pylori colonization may be even the marker of risk of malignancy development (Irazusta et al, 1998;Panella et al, 1996). Other authors (Diebold et al, 1998), however, demonstrated that during H.pylori colonization a decrease in the number of argyrophilic cells occurs along with simultaneous reduction of their proliferative potential.…”
Section: Analysis Of the Proliferative Activity Of Gastric Mucosa Glasupporting
confidence: 38%
See 1 more Smart Citation
“…Most cells deficient in MMR display a high level of genomic instability characterized by changes in simple repetitive sequences, so-called microsatellite instability (MSI). Chronic H pylori infection damages gastric barrier function [12,13] and stimulates gastric cell proliferation [14][15][16][17][18][19] , which leads to mucosal repair [20] , but which can also induce cellular DNA damage.…”
Section: Terminologymentioning
confidence: 44%
“…Most cells deficient in MMR display a high level of genomic instability characterized by changes in simple repetitive sequences, so-called microsatellite instability (MSI). Chronic H pylori infection damages the gastric barrier function [12,13] and stimulates gastric cell proliferation [14][15][16][17][18][19] , which leads to mucosal repair [20] , but which can also induce cellular DNA damage [18][19][20][21][22] . H pylori gastritis occurs more frequently in individuals with MSI-positive than MSI-negative gastric cancers, which raises the possibility that H pylori infection affects the DNA MMR system [23] .…”
Section: Introductionmentioning
confidence: 43%